Violent Victimization and Adolescents’ Attitudes Toward Romantic Relationships and Sexual Activity - Warner, Tara D. (Journal of interpersonal violence, 2022)
Violent victimization in adolescence spurs risk-taking behaviors (e.g., violent offending and substance use/abuse), undermines mental well-being, disrupts developmental transitions, and even has interpersonal and relational consequences. Adolescent victims initiate earlier and progress faster through sexual and romantic relationships. Because the reasons for the links between victimization and relationship behaviors remain unclear, we explored how violent victimization might shape how adolescents think and feel about intimate/romantic relationships. We focus specifically on interest in forming relationships and expectations about intimate/sexual activity occurring within relationships. Using data from the National Longitudinal Study of Adolescent to Adult Health (Add Health; n = 10,570 [54% girls; 56% non-Hispanic white; ages 11?18]), we found that adolescent victims of violence were more pessimistic about marriage and more favorable toward sexual activity, with patterns varying by age at victimization and gender. Late adolescent victims were marginally more interested in romantic relationships but were pessimistic about marriage. Early adolescent and girl victims were less favorable toward sexual activity in relationships, while later adolescent and boy victims were more permissive. Violent victimization may foster problematic attitudes toward intimate relationships, which may account for previously observed increased involvement in risky relational and sex behaviors.